PERANCANGAN SIMULASI DALAM PELAYANAN KESEHATAN: SIMULATION DESIGN IN HEALTHCARE - Yanty Rumengan (Universitas Papua, 2014)
Increased pressure to control costs and increased competition has prompted health care managers to look for tools to more effectively operate their institution. Managers are increasingly using simulation modeling to understand and to run their own process. A simulation model has been complemented with a series of decision making routines. These routines use a hierarchical approach to organize the various scenarios under which the model may run. This concept will present a simulation model of general in patients flow in a hospital. Simulation was used to analyze the inpatient flow. The main objective of this study was to determine the best way to optimize patient arrival at the hospital in order to reduce the queue of patients.